Examining the effect of childhood trauma on psychological distress, risk of violence and engagement, in forensic mental health. (30th December 2016) - Macinnes, Marlene; Macpherson, Gary; Austin, Jessica; Schwannauer, Matthias
Abstract: Previous research has found an association between childhood trauma and insecure attachment and psychological distress, risk of violence and engagement in therapy. The aim of this study was to investigate the relationships between these factors in a forensic population. Sixty-four participants from three secure psychiatric hospitals completed the Childhood Trauma Questionnaire (CTQ), the Relationship Scales Questionnaire (RSQ) and the Clinical Outcomes in Routine Evaluation – Outcome Measure (CORE-OM). Overall scores from participants' Historical Clinical Risk Management Violence Risk Assessment Scheme, (HCR-20) were calculated. Staff evaluated participants' engagement in therapy via completion of the Service Engagement Scale (SES). This retrospective study found childhood trauma and insecure attachment significantly predicted psychological distress and risk of violence. No associations with engagement were found, but methodological reasons for this outcome were acknowledged. The importance of routinely assessing for a history of childhood trauma and insecure attachment was highlighted. Highlights: This is a retrospective study of participants in secure hospitals. It examined childhood trauma, psychological distress, risk and engagement. Childhood trauma significantly predicted psychological distress and risk of violence. No associations with engagement were found. The benefits of routinely assessing for childhood trauma were highlighted.